PENGARUH HARGA, LOKASI DAN KUALITAS PELAYANAN DALAM MENARIK KEPUASAN KONSUMEN DENGAN MINAT BELI SEBAGAI VARIABEL INTERVENING PADA CAFE TEDUH SORE - Marsuki, Farukh Abdullah Huzain Risqy; Arief, Mohammad Yahya; Praja, Yudha (Fakultas Ekonomi dan Bisnis, 2024)
Globalization makes the world grow very quickly. Many business actors have emerged, causing an increase in the number of businesses with similar characteristics, resulting in very tight competition. So to deal with these situations and conditions, business actors must be able, fast and responsive in making decisions so that the business they build can develop optimally. Business actors are required to maintain the market and compete successfully. The aim of this research is to analyze the influence of price, location and service quality in attracting consumer satisfaction through purchase interest. This research is explanatory research. The population in this study were consumers of Cafe Teduh Sore in Situbondo. The sampling technique was determined by simple random sampling. Data analysis and hypothesis testing in this research used the Partial Least Square Structural Equation Model (PLS-SEM). The results of the direct influence hypothesis test using the Smart PLS 3.0 application, show that Price has a significant positive effect on Purchase Interest, Location has a negative but not significant influence on Purchase Interest, Service Quality has a significant positive influence on Purchase Interest, Price has a positive but not significant influence on Consumer Satisfaction, Location has a negative but not significant effect on consumer satisfaction, Service quality has a positive but not significant effect on consumer satisfaction, Purchase interest has a significant positive effect on consumer satisfaction, Price has a significant positive effect on consumer satisfaction through purchase intention, Location has a negative but not significant effect on consumer satisfaction. Consumer satisfaction through purchase interest. Service quality has a positive but not significant effect on consumer satisfaction through purchase interest.